The Influence of Electronic Word of Mouth Through Tiktok Social Media Platform on Consumer Purchase Intention on Beauty Products Scarlett Whitening In Bandung City - Christy, Emily; Sirait, Tongam (Devotion : Journal of Research and Community Service, 2024)
This study examines the impact of Electronic Word of Mouth (e-WOM) on TikTok regarding Scarlett Whitening products and their influence on Purchase Intention. The objectives are to evaluate the effects of Information Quality, Information Quantity, Information Credibility, Information Usefulness, and Review Valence on Purchase Intention, mediated by Information Usefulness and Information Adoption. Using Partial Least Squares Structural Equation Modeling (PLS-SEM) and SmartPLS 3.0, data from 210 Generation Z and millennial respondents in Bandung were analyzed. The findings reveal that Information Quality, Quantity, Credibility, and Review Valence significantly enhance Information Usefulness, which in turn positively affects Information Adoption and Purchase Intention. High-quality, credible, and well-quantified information along with constructive reviews significantly improve user perception of usefulness, leading to higher information adoption and ultimately boosting purchase intention. These insights are crucial for marketers to design effective information strategies on TikTok to enhance consumer decision-making and increase product sales. Future research should incorporate additional variables such as trust and brand image to further understand their influence on purchase intention.